Características químico-mineralógicas e cerâmicas da matéria-prima utilizada pelo polo cerâmico de Rio Verde de Mato Grosso, MG - Montibeller, Cibele Carolina [UNESP] (2015)
The Ceramic Region of Rio Verde de Mato Grosso (MS) uses as raw material sedimentary rocks attributed to Ponta Grossa Formation (Devonian, Paraná Basin). This region produces bricks, roof tiles, rustic ceramic tiles of cotto type, using extrusion processes. Due to defects present in their products, a medium-sized ceramic industry, located in Rio Verde de Mato Grosso, requested aid to determine the causes for defects, aiming to solve, control or minimize production losses. Preliminary studies show that part of the production problems are related to mineralogical, textural and chemical aspects of raw material, which should be best characterized. The objectives were achieved through geological survey carried out in the Rio Verde de Mato Grosso-Coxim region, to detail the identified rock types (shales, siltstones, mudstones and sandstones) and collect representative samples, to permit petrographic, mineralogical and chemical analysis and technological tests. These rock types are composed of kaolinite, illite and/or thin mica, quartz and detrital feldspars with very fine sand grain to fine silt and its contaminants: organic matter, pyrite nodules and/or iron oxy-hydroxides, carbonatic and phosphatic levels, veins consisting of calcium sulfate and calcium carbonate, and sulfates and calcium carbonate efflorescence. Based on the above, this work intends to characterize, on the mineralogy, texture, chemical composition and ceramic behavior, the different rock types belonging to the Ponta Grossa Formation, which outcrops in ceramic region of Rio Verde de Mato Grosso